A smart single molecular probe for Cu2+/Fe3+/Mg2+ by three-emission behaviors. (December 2019) - Wang, Fang; Li, Chunhui; Song, Lingyun; Zhang, Xiuling; Wang, Aili; Zhou, Lianwen; Jia, Chunxiao; Xu, Jing; Chen, Yuting
Abstract: An azacrown[NS2 O2 ]-azastyryl-modified fluorene probe (AC-AS-F) has been designed and synthesized. Systematic optical studies show that AC-AS-F displays a distinct two-step fluorescence response to the increasing quantity of Cu 2+ : The fluorescent emission of this compound centered at 490 nm is first blue-shifted to 450 nm with a concomitant increase in fluorescence intensity and then is only enhanced along with successive increase in Cu 2+ amount from 0 to 1 and 1–2 equiv. In contrast, addition of Fe 3+ leads to just an opposite manner in the fluorescence spectrum: the corresponding fluorescence emission is red-shift to 540 nm simultaneously accompanied by a obvious decrease in fluorescence intensity. After adding Mg 2+, the maximum fluorescence emission of AC-AS-F is red-shifted to 510 nm synchronously but with a little decrease in the fluorescence intensity. Meanwhile AC-AS-F also displays three obviously distinct absorption behaviors with diverse absorption-ratiometric signals upon respective addition of Cu 2+, Fe 3+ or Mg 2+, which induce an obvious change in the solution color from pale yellow to yellowish-brown and then to dark yellow upon successive addition of Mg 2+, Cu 2+ and Fe 3+ . These, together with the dual optical responses to the metal displacement of AC-AS-F-M(M = Cu 2+ /Mg 2+ ) by Fe 3+ /Cu 2+, endow AC-AS-F the multi-stimuli-channel sensing nature for these metal ions, in particular for Cu 2+ and Fe 3+ with fast-response function. Graphical abstract: A smart azacrown[NS2 O2 ]-azastyryl-modified fluorene probe exhibits three discriminating fluorescence emission behaviors as well as absorption-ratiometric signals for Cu 2+, Fe 3+ and Mg 2+, which, together with dual optical responses to the metal displacement of AC-AS-F-M(Cu 2+ /Mg 2+ ) complex by Fe 3+ /Cu 2+, endows this compound the multi-stimuli-channel sensing nature for these metal ions, in particular for Cu 2+ and Fe 3+ with fast-response function.Image 1 Highlights: The smart easy-to-synthesize fluorene probe consists of two conjugated N-containing receptors. This fluorene probe displays three distinct fluorescence and absorption responses to Cu= 2+ /Fe 3+ /Mg 2+ . There exists different binding mode between AC-AS-F and these three metal ions.